Influence of Predisposing, Enabling, and Reinforcing Factors on the Election of Seeking of Birth Attendant in Health Care Community of Kota Padang in 2018 - B, Chandra; ., Sridiany; H, Hendri (KnE Life Sciences, 2019)
Background: Health behavior based on the predisposing, enabling, and reinforcing factor (Skinner, citPurwanto, 1999), as well as the search behavior of childbirth. Childbirth helpers can be brought from amongst health workers or non-health workers (shaman). At the time of the PKM work in Padang City, while conducting a pregnancy checkup, the delivery was conducting an examination on the traditional birth attendant which was called the culture of seeing. In the Kota Padang healthcare, there are still 20 people of shaman in 10 villages. Problem Formulation: Are there any possible influences of predisposing, enabling, and reinforcing factors to the Election of seeking the birth attendant in the healthcare community of Kota Padang in 2018? Research Objectives: To analyze the influence of predisposing, enabling, and reinforcing factors to the Election of seeking birth attendants in the healthcare community of Kota Padang in 2018. Research Methods: This research used mixed methods of quantitative and qualitative researches. Accidental sampling was taken from 76 people. Bivariate analysis was done using the Chi-Square Test formula, using significance or with a 95% confidence level (ά = 0.05). Qualitative analysis used content analysis. Research Results: There is a relationship between the knowledge and beliefs of respondents to non-health workers (P = 0.00) with birth assistance plans. There is a relationship between household facilities and related facilities (P = 0.00), and there is also a relationship between the satisfaction of services by health workers and plans for delivery assistance (P = 0.016). There is a relationship between decision-making with the selection of delivery assistance (P = 0.045). Suggestion: It is necessary to have health promotion programs related to the prevention of complications of pregnancy and childbirth in the Lembak tribe. Health promotion should be more concerned with the socio-cultural aspects that can still be overcome by the people of the Lembak tribe in the Rejang Lebong district.